- #1

evosy1978

- 6

- 0

Ive was reading my literature today and it showed me some algebra, which i did not understand how it went from one step to the next...

What was done to simplify

V= x^2 ( 75-x^2 / 2x ) into V= x/2 ( 75-x^2 )

& then what was done to simplify ^^^

V= x/2 ( 75-x^2 ) into V= 1/2 ( 75x-x^3 )

(for anyone interested the above has now been differentiated)

I would now like to know when finding x how they go from

1/2 ( 75-3x^2 ) = 0 to this 75 = 3x^2

Thanks for any help. I know I'm missing something simple here?